Community-Based Tourism Development Strategies at Lejja Hot Springs Soppeng Regency - Zulfachry, Zulfachry; Rachmat, Zul (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to analyze the implementation of Community-Based Tourism (CBT) around Lejja Hot Springs in Soppeng Regency, South Sulawesi. The main focus of this research is to explore the role of local government and the community in managing the tourism destination and to assess the economic, social, and environmental impacts of community-based tourism development in the area. A qualitative approach was used in this research, with data collection techniques including in-depth interviews with government officials, tourism operators, and local community members, along with direct observation at the site. The findings show that active community participation in tourism planning and management has led to positive impacts on economic empowerment and the preservation of local culture. However, challenges such as limited infrastructure, lack of training for the community, and environmental management issues still pose significant barriers to further development. This study is expected to provide recommendations for stakeholders to enhance the sustainability of community-based tourism at Lejja.